Supravalvular pulmonary stenosis 9 years after surgically created pleuro‐pericardial window. Issue 1 (14th October 2020) - Mishra, Anand Kumar; Kumar, Vikas; Mandal, Banashree; Gourav, Krishna Prasad
Abstract: Supravalvular pulmonary stenosis acquired as a postoperative cardiac procedure complication is relatively common. However, that occurring after a surgically created pleuro‐pericardial window has not been described until now, to the best of our knowledge. We present a case of acquired supravalvular pulmonary stenosis that developed 9 years after the pleuro‐pericardial window creation for pyopericardium due to a constricting pericardial band. The child underwent successful surgical relief of the stenosis along with repair of the atrial and ventricular septal defects.